A comparison of project participants' and extension officers' perceptions and knowledge of participation in agricultural projects in the North West Province South Africa - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.